The Application and Legality of Telemedicine during a Pandemic Covid 19 in North Sumatra - Sidi, Redyanto; Maela, Irda Rienta; Khaliludin, Khaliludin; Dwisartika, Hutri Ayu; Ramadhan, Aulia; Prasetyo, Reza F (Budapest International Research and Critics University, 2021)
The government through the Minister of Health has issued the Decree of the Minister of Health Number Hk.01.07/Menkes/4829/2021 concerning Guidelines for Health Services through Telemedicine during the 2019 Corona Virus Disease Pandemic. The design of this study was a systematic review by systematically viewing journals and articles on Google Scholar, garuda portal, and science direct and compared with the laws in force in Indonesia regarding telemedicine. The inclusion criteria in this study were journal publications spanning the years 2011-2021. The application of telemedicine services in Indonesia has not maximized the legal aspects that protect the confidentiality of patient data and patient problems. The Indonesian telemedicine service application does not guarantee the confidentiality of patient data. Telemedicine services have not been fully implemented in Indonesia because internet access services have not been evenly distributed in all regions. Telemedical application developers must pay attention to matters that have legal implications in order to protect the interests of patients and the interests of service providers.